ANALISIS PENGARUH FAKTOR-FAKTOR TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA BISNIS PERUSAHAAN (Studi Pada Empat Pabrik Gondorukem Terpentin Perhutani Unit 1 Jawa Tengah) - Dananjaya, Raffi Hakim; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2015)
Quality is important for companies to be able to compete with other companies. The selection of proper management strategies made firm can increase the business performance. The strategy of integrated quality management or Total Quality Management (TQM) can be an option to maintain and improve the quality of the products of a company's business performance. This study aims to analyze the influence of the independent variables management leadership, customer focus, information and analysis, process management, product design, and continuous improvement of the dependent variable business performance on the millÂ gondorukem turpentineÂ Perhutani Unit 1 Central Java. The population in the study was 187 employees from four factory gondorukem turpentine Perhutani Unit 1 Central Java. The sample used in this study as many as 130 employees from four factory gondorukem turpentine Perhutani Unit 1 Central Java. Model analysis using multiple linear analysis and tools to process data using SPSS 20 for windows. The result of the analysis indicate that management leadership, customer focus, information and anlisis, process management, product design, and continuous improvement have a positive and significant influence to business performance. The company's business performance will be improved if the company can improve the quality of its products. With the implementation of TQM, vision and mission can be achieved, decision-making and problem solving are influenced by all parties, The fulfillment expectation of consumers, and eliminating defective products so that waste can be eliminated and will increase profits for the company.